A Method to Estimate the Horizontal Handover Decision Effect on Indoor Wireless Conversational Video Quality. (25th May 2008) - Fernandez Duran Fernandez Duran, Alfonso Alfonso; Perez Leal Perez Leal, Raquel Raquel; Alonso Alonso, Jose I. Jose I.
Abstract : One of the most interesting and valuable services considered in fixed mobile convergence is video telephony. The success of this conversational video service will depend on the conversational video quality achieved in the multicell wireless indoor scenarios. One of the essential elements in the quality is the effect of the horizontal handovers in the conversational video. This paper analyzes the handover decision based on the probability calculation of handover events in the case of relative signal strength with hysteresis threshold (RSSHT) approach, and it proposes a new handover decision mechanism, variable hysteresis, to avoid unnecessary handovers. The paper presents the impact of the number of handovers and their duration time on the video's effective frame rate. Moreover, the effect of video stream modification during a short handover is also analyzed. Probability and handover duration approaches are combined and a new simple method for video quality evaluation is caused by the handovers in multicell indoor WLAN scenarios. Finally, the model proposed has been applied to a real office scenario.